Safety and effectiveness of bevacizumab in the treatment of malignant gliomas - Molas, Gloria; doPazo-Oubiña, Fernando; Anglada-Martinez, Helena; Riu-Viladoms, Gisela; Creus-Baro, Natalia (European Journal of Oncology and Environmental Health, 2015)
Aim: The prognosis of malignant glioma is poor owing to the rapid and fatal progression of the disease. After surgery, few therapeutic options are available. Bevacizumab, a monoclonal antibody against vascular endothelial growth factor, has been proposed as an alternative treatment for recurrence. The aim of this study is to evaluate the safety profile of bevacizumab administered as part of the routine care of patients with malignant glioma at a tertiary level hospital. Patients and methods: Observational retrospective study. The study sample comprised patients who received at least one dose of bevacizumab for the treatment of malignant glioma from January 2009 to June 2012 at Hospital Clinic,Barcelona,Spain. Medical records were reviewed. The primary endpoint was the percentage of patients with adverse reactions. Results: The final sample comprised 27 patients, of whom 21 were diagnosed with glioblastoma. At least one adverse reaction was detected in 74% of patients, and a severe adverse reaction was detected in 30%. Adverse reactions led to hospitalization in 18.5% of cases. Only 11.1% stopped treatment because of toxicity. Median time to progression was 2.8 months (interquartile range, 3.5; censored data, 14.8%). Median overall survival was 12.2 months (interquartile range, 12.8; censored data, 63.0%). Conclusions: The safety profile of bevacizumab in routine clinical practice is similar to that observed in clinical trials. The drug is well tolerated, although it can produce severe adverse reactions. In addition, bevacizumab seems to be less effective in patients with grade III glioma.